2023
DOI: 10.1186/s13075-023-03161-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of glycolysis and glutaminolysis for synergistic therapy of rheumatoid arthritis

Shanzay Ahmed,
Christopher B. Mahony,
Alyssa Torres
et al.

Abstract: Background Synovial fibroblasts in rheumatoid arthritis (RAFLS) exhibit a pathological aberration of glycolysis and glutaminolysis. Henceforth, we aimed to investigate if dual inhibition of these pathways by phytobiological compound c28MS has the potential of synergistic therapy for arthritis by targeting both glucose and glutamine metabolism. Methods The presence of HK2 and GLS across various cell types and associated gene expression in human syno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…However, the proteins in the water extract of Kampo medicines (or crude drugs) are often low and may be undetectable. When researchers investigate intracellular or tissue proteins in vitro or in vivo, Western blot with SDS-PAGE [22,26] and ELISA [27,28] are commonly used to identify or quantify the individual proteins (e.g., interleukin-1, tumor necrosis factor-α, and matrix metalloproteinase) [79][80][81]. The volume of samples and reagents used is 10-30 µL per SDS-PAGE well and 50-200 µL per ELISA well.…”
Section: Previous and Potential Technologies For The Identification A...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the proteins in the water extract of Kampo medicines (or crude drugs) are often low and may be undetectable. When researchers investigate intracellular or tissue proteins in vitro or in vivo, Western blot with SDS-PAGE [22,26] and ELISA [27,28] are commonly used to identify or quantify the individual proteins (e.g., interleukin-1, tumor necrosis factor-α, and matrix metalloproteinase) [79][80][81]. The volume of samples and reagents used is 10-30 µL per SDS-PAGE well and 50-200 µL per ELISA well.…”
Section: Previous and Potential Technologies For The Identification A...mentioning
confidence: 99%
“…Accordingly, we evaluated the applicability and suitability of conventional technologies for the separation, detection, identification, and quantification of proteins in Kampo medicines [22][23][24]. We found that, given the insufficient crude sample volume, column chromatography [22,25], electrophoresis [22,26], and enzyme-linked immunosorbent assay (ELISA) [27,28] may be unsuitable for detecting rare proteins within the extract in Kampo medicines. Hence, we focused on membrane chromatography, where samples can repeatedly flow against the membranes, facilitating the collection and separation of proteins [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the presence of glutamine potentially influences the rate of the glycolytic pathway by fuelling the TCA cycle, which in turn draws more pyruvate into the mitochondria, facilitating the processing of pyruvate generated from glycolysis. Given this interplay, along with evidence that shows an upregulation of the kinetics of both pathways in various disorders [15,16], recent fluxomic studies encourage the simultaneous monitoring of the kinetics of these two pathways [17][18][19]. Considering that cells often adapt their metabolic rates and switch between pathways such as glycolysis and glutaminolysis in response to local environmental conditions, the kinetic nature of these processes emphasises the necessity for real-time and in situ monitoring.…”
mentioning
confidence: 99%